Immunothrombosis in Acute Respiratory Dysfunction of COVID-19 - Fang, Xiang-Zhi; Wang, Ya-Xin; Xu, Ji-Qain; He, Ya-Jun; Peng, Zhe-Kang; Shang, You (Frontiers in Immunology, 2021)
COVID-19 is an acute, complex disorder that was caused by a new β-coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Based on current reports, it was surprising that the characteristics of many patients with COVID-19 who fulfil the Berlin criteria for acute respiratry distress syndrme (ARDS), are not always like those of patients with typical ARDS and can change over time.While the mechanisms of COVID-19-related respiratory dysfunction in COVID-19 have not yet been fully elucidated. pulmonary microvascular thrombosis is involved is speculated to be involved. Considering that thrombosis is highly related to other inflammatory lung diseases, immunothrombosis, a two-way process that links coagulation and inflammation, seems to be involved in the pathophysiology of COVID-19, including respiratory dysfunction. Thus, the current manuscript will describe the proinflammatory milieu in COVID-19, summarize current evidence of thrombosis in COVID-19, and disscues possible interactions between these two.